Strengthening health care research and academics during and after COVID19 pandemic- an Indian perspective - Aman Chowdhry, Professor, MDS; Priyanka Kapoor, Professor, MDS; Deepika Bablani Popli, Professor, MDS (Journal of Oral Biology and Craniofacial Research)
The world-wide crisis of COVID-19 pandemic has disrupted daily lives, global economies, intra/inter-countries political outlook and educational systems. Schools and colleges in India and abroad are under lock-down to maximize social distancing and minimize the spread of infection amongst students and teaching staff. Health sciences related universities and researchers are forced to adopt non-contact teaching and research.Present article highlights the positive impact and opportunities provided by COVID-19 crisis to health care research and academic set-up. We have compiled ethical, effective and practical guidelines to mitigate the impact on health care related research and academic front during these pandemic times in an Indian perspective. These guidelines and management suggestions can be modified to suit region based cases and can be applied in global perspective also.The suggestions in the current article provide a working collaboration of students and teachers to effectively connect on virtual platforms to strengthen their research output, giving suggestions of data-sharing and rapid review of proposals by online review ethical boards. This time is proposed to be used for generating a positive impact on health and research sector to use each adversity as an opportunity.